Floreal : magazine universel illustré de la famille - édition mensuelle (Paris: Floreal)
"Periodiciteit: maandelijksHoofdredactie: CoquelicotRedactie: J.F. Louis Merlet, J. Grand-Carteret, L. Guilloux, Ch. Chamir, F. Clar, M. Gauthier, J. Rivet, J. Valmondois, E. Guillaumin, M. RenardBeheer/Administratie: Boulevard Raspail 95, Paris-6e"